Porokeratosis ptychotropica: a rare case report with unusual presentation - K., Sangheetha; A., Raja Shareef; N., Azeem Jaffer (International Journal of Research in Medical Sciences, 2018)
Porokeratosis is a rare disorder of epidermal keratinization characterized clinically by annular plaque with thread like hyperkeratotic border with a central groove that expand centrifugally and this border corresponds to coronoid lamellae histologically which are the columns of parakeratosis that overlie an epidermal invagination with loss of granular layer and dyskeratosis of upper spinous keratinocytes. The disorder was erroneously named porokeratosis because the coronoid lamella was initially described as being present over a sweat pore, which is a fixed structure that cannot expand peripherally. Five primary clinical variants have been described: classic porokeratosis of mibelli, disseminated superficial actinic porokeratosis, linear porokeratosis, punctate porokeratosis and porokeratosis palmaris et plantaris disseminate. Porokeratosis ptychotropica one of the rare variants of porokeratosis described by lucker et al which has been added recently in the classification. It is characterized clinically by symmetrical verrucous papules and plaques resembling psoriasis plaque in the gluteal cleft, buttocks and rarely extends to genitalia and histologically by multiple coronoid lamella. We report a case of 43year old female, presented with 10years duration of pruritic raised skin lesion over the left gluteal region. Dermatological examination revealed single well defined erythematous scaly plaque with central atrophy, hyperpigmentation and peripheral thread like elevated border. Histopathological examination revealed multiple coronoid lamella which is the hallmark for porokeratosis ptychotropica, confirmed the diagnosis. The patient was treated with 5-fluorouracil cream. we report this case due to its rarity and the unusual presentation of single plaque of porokeratosis ptychotropica.